Peptide-Based Subunit Vaccine against Hookworm Infection - Skwarczynski, Mariusz (Public Library of Science, 2012)
Hookworms infect more people than HIV and malaria combined, predominantly in third world countries. Treatment of infection with chemotherapy can have limited efficacy and re-infections after treatment are common. Heavy infection often leads to debilitating diseases. All these factors suggest an urgent need for development of vaccine. In an attempt to develop a vaccine targeting the major human hookworm, Necator americanus, a B-cell peptide epitope was chosen from the apical enzyme in the hemoglobin digestion cascade, the aspartic protease Na-APR-1. The A(291)Y alpha helical epitope is known to induce neutralizing antibodies that inhibit the enzymatic activity of Na-APR-1, thus reducing the capacity for hookworms to digest hemoglobin and obtain nutrients. A(291)Y was engineered such that it was flanked on both termini by a coil-promoting sequence to maintain native conformation, and subsequently incorporated into a Lipid Core Peptide (LCP) self-adjuvanting system. While A(291)Y alone or the chimeric epitope with or without Freund’s adjuvants induced negligible IgG responses, the LCP construct incorporating the chimeric peptide induced a strong IgG response in mice. Antibodies produced were able to bind to and completely inhibit the enzymatic activity of Na-APR-1. The results presented show that the new chimeric LCP construct can induce effective enzyme-neutralising antibodies in mice, without the help of any additional toxic adjuvants. This approach offers promise for the development of vaccines against helminth parasites of humans and their livestock and companion animals.